Brilliant interview : what employers want to hear and how to say it - Jay, Ros (Prentice Hall, 2011)
What do interviewers really want from a candidate? How do they decide whether to hire you or someone else? What can you do to make it you? Full of examples, quizzes, horror stories and tips, this book is clear enough for new interviewees, and has enough detail and ideas to revamp the technique of those more practised at job interviews.